Cosmology and CPT violating neutrinos - Gabriela Barenboim; Jordi Salvado (European Physical Journal C: Particles and Fields, 2017)
Abstract The combination charge conjugation–parity–time reversal (CPT) is a fundamental symmetry in our current understanding of nature. As such, testing CPT violation is a strongly motivated path to explore new physics. In this paper we study CPT violation in the neutrino sector, giving for the first time a bound, for a fundamental particle, in the CPT violating particle-antiparticle gravitational mass difference. We argue that cosmology is nowadays the only data sensitive to CPT violation for the neutrino–antineutrino mass splitting and we use the latest data release from Planck combined with the current baryonic-acoustic-oscillation measurement to perform a full cosmological analysis. To show the potential of the future experiments we also show the results for Euclid, a next generation large scale structure experiment.